2011
DOI: 10.1007/s10464-011-9486-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Cultural Adjustment and Trauma Services (CATS): Generating Practice‐Based Evidence on a Comprehensive, School‐Based Mental Health Intervention for Immigrant Youth

Abstract: A collaborative study of Cultural Adjustment and Trauma Services (CATS), a comprehensive, school-based mental health program for traumatized immigrant children and adolescents, was conducted to generate practice-based evidence on the service delivery model across two school districts. Program effectiveness was assessed by testing whether client functioning and PTSD symptoms improved as a result of 7 separate service elements. An array of clinical services including CBT, supportive therapy, and coordinating ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
124
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(127 citation statements)
references
References 44 publications
(93 reference statements)
1
124
0
2
Order By: Relevance
“…Three studies (Beehler et al, 2012;Kataoka et al, 2003;Mo¨hlen et al, 2005) reported significant reductions in symptoms of PTSD. Three studies reported an increase in social functioning (Beehler et al, 2012;Birman et al, 2008;Mo¨hlen et al, 2005), and two reported an increase in mental health utilization (Weine et al, 2008;Weine et al, 2003). Only two studies included family variables, such as family hardiness, as outcomes (Weine et al, 2008;Weine et al, 2003).…”
Section: Effectiveness Of the Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies (Beehler et al, 2012;Kataoka et al, 2003;Mo¨hlen et al, 2005) reported significant reductions in symptoms of PTSD. Three studies reported an increase in social functioning (Beehler et al, 2012;Birman et al, 2008;Mo¨hlen et al, 2005), and two reported an increase in mental health utilization (Weine et al, 2008;Weine et al, 2003). Only two studies included family variables, such as family hardiness, as outcomes (Weine et al, 2008;Weine et al, 2003).…”
Section: Effectiveness Of the Interventionsmentioning
confidence: 99%
“…Three of the studies were nonexperimental (Beehler et al, 2012;Birman et al, 2008;Weine et al, 2003), that is, they included only pretest and posttest evaluations (no control group). One study (Mo¨hlen et al, 2005) was quasi-experimental (included a control group) and two (Kataoka et al, 2003;Weine et al, 2008) employed a randomized controlled trial (comparison group and randomization).…”
Section: Study Designsmentioning
confidence: 99%
“…1 below) (Beehler, Birman, & Campbell, 2012;Pumariega, Rothe, & Pumariega, 2005). Many struggle with difficulties that were already present in the country of origin, for example, violence, social inequality, and poor education, and the new ones from the host country like acculturation, plus the lack of family and social networks (Glick & Clark, 2012).…”
Section: Risk Factorsmentioning
confidence: 99%
“…4 below), less external support and more susceptibility to chronic stress (Beehler, Birman, & Campbell, 2012;Martin, Liem, Mok, & Xu, 2012). Considered a multidimensional phenomenon, social inequality endangers the individuals' physical and mental health (Alley et al, 2006;Chen, Cohen, & Miller, 2010;D'Angiulli, Lipina, & Olesinska, 2012;Evans & Kim, 2013), predisposing to learned helplessness (Abramson, Seligman, & Teasdale, 1978) and hopelessness (Bolland, 2003), increasing vulnerability and impeding the development of resilience (Chen, Cohen, & Miller, 2010;Werner & Smith, 1992).…”
Section: Academic and Work Competencementioning
confidence: 99%
“…The significant burdens and challenges that socially disadvantaged groups experience increase the risk for psychological issues. (Beehler, Birman, & Campbell, 2012;Pumariega, Rothe, & Pumariega, 2005). Not only that, all too often immigrant women and children find themselves in a weaker position becoming targets from frustrated family heads (Erez, 2000;Erez, Adelman, & Gregory, 2009).…”
Section: Immigrants In Spainmentioning
confidence: 99%